Antagonism of cytotoxic T lymphocyte-mediated lysis by natural HIV-1 altered peptide ligands requires simultaneous presentation of agonist and antagonist peptides. - Sewell, A; Harcourt, G; Goulder, P; Price, D; Phillips, R (1997)
Mutations in human immunodeficiency virus (HIV) cluster in cytotoxic T lymphocyte (CTL) epitopes (Phillips, R. E. et al., Nature 1991. 354: 453) and are subject to immune-mediated positive selection (Price, D. A. et al., Proc. Natl. Acad. Sci. USA 1997. 94: 1890). We studied the effects of naturally occurring mutations in the HIV-1 p17 Gag HLA A2 restricted epitope SLYNTVATL on recognition by anti-HIV CTL. Most of these naturally occurring mutants escaped killing by one CTL line and the majority acted as CTL antagonists. We also investigated whether CTL exposed to a strict antagonist peptide restricted by HLA A2 were unresponsive when exposed to targets presenting the wild-type sequence. The results show that antagonism of anti-HIV CTL killing requires the simultaneous presence of agonist and antagonist peptide. We found no evidence that CTL exposed to an antagonist received a functionally negative signal since these CTL retained an unimpaired capacity to lyse targets bearing wild-type peptide.